Goering injuries: epidemiological, lesional and therapeutic aspects in the departments of Borgou and Alibori in Benin - Sambo, Bio Tamou; Hondonou, Adrien M.; Hadonou, Armel A.; Djego, Marcwell D.; Allode, Alexandre S. (International Surgery Journal, 2022)
Background: Traumatic lesions by goring constitute a particular entity regarding their lesion mechanism and their types which are different from civil traumatology. Objectives of current study was to investigate the epidemiological, lesional and therapeutic aspects of goring injuries in the departments of Borgou and Alibori in Benin. Methods: This was a prospective and descriptive study covering the period of eighteen months (January 2020 to June 2021) taking into account all patients admitted for goring trauma to one of the reference hospitals. Results: A total of 40 cases were identified. The average age of the subjects was 20.1±14.4 years with extremes of 7 and 65 years. The male subject was the most affected (97.5%) with a sex ratio of 39/1. The age group of 10 to 15 years was the most affected with 19 (47.5%) cases. Goering often took place on pasture (45%) or in the field (35%) and oxen were the most involved animal (90%). The victims were often herdsmen or farmers in respectively 50% and 37.5% of the cases. The trauma was most often located in the abdomen (35%). The treatment depended on the lesions. The average hospital stay was 3.9±3 days with extremes of 1 to 16 days. Two patients had died, so a mortality rate of 5%. Conclusions: The prevention of these traumas passes by the schooling of the children.